The first successful application of preimplantation genetic diagnosis for hearing loss in Iran - Karimi Yazdi, Alireza; Davoudi-Dehaghani, Elham; Rabbani Anari, Mahtab; Fouladi, Paanti; Ebrahimi, Elmira; Sabeghi, Solmaz; Eftekharian, Ali; Fatemi, Kiyana Sadat; Emami, Hamed; Sharifi, Zohreh; Ramezanzadeh, Fatemeh; Tajdini, Ardavan; et al. (Cellular and Molecular Biology, 2018)
Hearing impairment (HI) caused by mutations in the connexin-26 gene (GJB2) accounts for the majority of cases with inherited, nonsyndromic sensorineural hearing loss. Due to the illegality of the abortion of deaf fetuses in Islamic countries, preimplantation genetic diagnosis (PGD) is a possible solution for afflicted families to have a healthy offspring. This study describes the first use of PGD for GJB2 associated non-syndromic deafness in Iran. GJB2 donor splicing site IVS1+1G>A mutation analysis was performed using Sanger sequencing for a total of 71 Iranian families with at least 1 deaf child diagnosed with non-syndromic deafness. In Vitro Fertilization (IVF) was performed, followed by PGD for a cousin couple with a 50% chance of having an affected child. Bi-allelic pathogenic mutations were found in a total of 12 families ( 17 %); of which a couple was a PGD volunteer. The deaf woman in this family was homozygous and her husband was a carrier of the IVS1+1G>A gene mutation. Among 8 biopsied embryos, two healthy embryos were implanted which resulted in a single pregnancy and subsequent birth of a healthy baby boy. This is the first report of a successful application of PGD for hearing loss in Iran. Having a baby with a severe hearing impairment often imposes families with long-term disease burden and heavy therapy costs. Today PGD has provided an opportunity for high-risk individuals to avoid the birth of a deaf child.